Proceedings of the Hong Kong international workshop on statistics and finance : (Imperial College Press, 2000)
Proceedings of the Hong Kong International Workshop on Statistics and Finance: An Interface, held in Hong Kong, on July 4-8, 1999. Contents include long memory and value at risk, volatility, forecasting, applications, and more.